TEACHING STUDENTS TO DEVELOP PARAGRAPHS BY POETRY WRITING - Mahmud, Murni (Universitas Negeri Makassar, 2017)
The use of literary work such as poetry, prose, or drama in English language teaching is recognized as powerful media to teach English language skills. This is commonly known as creative writing, which has recently become important subject in English language teaching. This study had examined the use of English poetry writing in English language teaching, particularly in teaching English writing skills. There are two main points of discussion in this paper, namely the analysis of the students? ability to write poetry in English and the effectiveness of that poetry writing in teaching English writing skills. The study was conducted at the third semester students majoring in English Education at the State University of Makassar, Indonesia. To find data about students? ability in poetry writing, a test was given and the results were analyzed descriptively. To find data about the effectiveness of poetry writing in teaching English writing skills, a quasi-experimental design with a t-test was employed. Findings reveal the students? good ability in writing poetry in English. Aspects of poetry such as imagery, rhyme, rhythm, and sound devices can be seen in the poetry written by students. Poetry writing also has an effective function in teaching English, particularly in developing students? writing skills. Poetry made by the students can invite more ideas to write. Students taught to write poetry in English and asked to develop writing based on that written poetry demonstrate better achievement than those who were not taught by poetry writing.